Antagonism of FOG-1 and GATA factors in fate choice for the mast cell lineage - Cantor, Alan B. (The Rockefeller University Press, 2008)
The zinc finger transcription factor GATA-1 requires direct physical interaction with the cofactor friend of GATA-1 (FOG-1) for its essential role in erythroid and megakaryocytic development. We show that in the mast cell lineage, GATA-1 functions completely independent of FOG proteins. Moreover, we demonstrate that FOG-1 antagonizes the fate choice of multipotential progenitor cells for the mast cell lineage, and that its down-regulation is a prerequisite for mast cell development. Remarkably, ectopic expression of FOG-1 in committed mast cell progenitors redirects them into the erythroid, megakaryocytic, and granulocytic lineages. These lineage switches correlate with transcriptional down-regulation of GATA-2, an essential mast cell GATA factor, via switching of GATA-1 for GATA-2 at a key enhancer element upstream of the GATA-2 gene. These findings illustrate combinatorial control of cell fate identity by a transcription factor and its cofactor, and highlight the role of transcriptional networks in lineage determination. They also provide evidence for lineage instability during early stages of hematopoietic lineage commitment.